MASTERING THE TOOLS OF CITATION DATABASES IN HIGHER MEDICAL EDUCATION - H. Morokhovets; Yu. Lysanets; L. Ostrovska; T. Purdenko (Проблеми екології та медицини)
In the contemporary academic setting, the quality of publications and the publication activity of a scientist, educational or research institution are evaluated using a set of scientific metric indicators. There are the following parameters: total citations, total number of links, the Hirsch index, impact factor, g-index, and-10 index. The aim of the paper is to cover the methods of working with the world scientific and metric databases of literature, as well as to explain the essence and algorithms for calculating the major scientific and metric indicators. We used the bibliosemantic research method in order to analyze the relevant scientific literature. The article describes the principles of mastering the tools of international databases Scopus, Web of Science, Google Scholar, Mendeley bibliographic manager, ORCID system. The paper focuses on the essence of scientific and metric indicators, calculated by these resources, as well as their scope and possibilities. The authors analyze the positive aspects of using the scientific metrics to determine the influence of a particular author or institution, as well as a number of subjective disadvantages of their widespread adoption in higher education. The modern tools for working with scientific information play a key role in the research activities of scientists, institutions of higher education, research institutions. The quality of publications is determined by a number of scientific metrics, calculated by authoritative scientific literature databases, such as Scopus and Web of Science. The h-indices are calculated in terms of publications in these bases, and serve as qualitative indicators for scientific activity evaluation. Scopus and Web of Science, in addition to their own built-in tools for searching, visualizing, analyzing and tracking data, integrated with the registers of scientists, bibliographic managers, plugins that allow to automate the processes of citation, lists of literature, preparation of publications according to the requirements of a specific edition, work with full-text versions of articles in different formats.